Penegakan Hukum Terhadap Tindak Pidana Perjudian Online Di Wilayah Hukum Kepolisian Resor Kampar - Salsabila, Vania Mahfira; Ardiyanto, Syaifullah Yophi; Andrikasmi, Sukamarriko (Jurnal Ilmiah Wahana Pendidikan, 2024)
Article 27 paragraph (2) of Law Number 19 of 2016 concerning Electronic Transaction Information contains a prohibition on gambling. The penalty for those who violate is imprisonment for a maximum of 6 years and/or a fine of a maximum of Rp. 1,000,000,000. In reality, the implementation of criminal sanctions has not been implemented optimally, because it can be seen that there are still many gambling cases occurringonline in Kampar Regency. Research purposes This thesis is to determine law enforcement, obstacles in law enforcement and efforts to overcome obstacles in law enforcement against criminal acts of gamblingonline in Kampar Regency. This type of research can be classified as a type of researchsociological, because the author directly conducted research at the location or field where he was researched in order to provide a complete and clear picture of the problem being studied. This research was conducted at the Kampar Police Department, meanwhilepopulation and sample is all parties related to the problem under study. In this researchdata source used primary data and secondary data and tertiary data, and data collection techniques in this research using interviews and literature study. From the research results there are three main things that can be concludedFirst, law enforcement carried out by the Kampar Police is through preventive and repressive efforts.Second,Some of the obstacles faced by the police are the failure to find evidence, changing bank accounts/fictitious data, the increasing level of human capability in technology, obstacles to law enforcement, lack of public legal awareness, units that handlecybercrime only up to the Regional Police level.Third,Efforts made to overcome obstacles to law enforcement include providing legal outreach/counseling by collaborating with the community, increasing the ability of police officers regarding technology and information, increasing supervision/patrols directly to the community or through cyberspace so that law enforcement can be carried out optimallyThird,The role of the community is needed to assist law enforcement officers in tackling criminal acts of online gambling.